Life and scientific activity of an engineer-railroader V. O. Sokovych on the background of the historical events of 1930s - Fesovets, O. R. (History of science and technology, 2017)
This article contains the work of the scientist-railwayman Volodymyr SOKOVYCH industrialization during the 30s of the twentieth century, his position in the scientific discussions on the development of railway transport is illuminated, as well as an overview of the theoretical developments of the scientist to organize rail transport, taking into account the militarization of the Soviet Union.